Fixed points for several classes of mappings in variable Lebesgue spaces. (3rd June 2021) - Domínguez Benavides, T.; Moshtaghioun, S. M.; Sadeghi Hafshejani, A.
ABSTRACT: The variable Lebesgue spaces are a generalization of the classical Lebesgue spaces, replacing the constant exponent p with a variable exponent function p ( ⋅ ) . Beside their intrinsic interest, they are also very important for their applications to partial differential equations and variational integrals with non-standard growth conditions. In this paper, we study some properties related to the existence of a fixed point for several classes of mappings defined on these spaces, considering both the modular and its induced norm.